Celecoxib: considerations regarding its potential disease-modifying properties in osteoarthritis - Zweers, Manon C (BioMed Central, 2011)
Osteoarthritis (OA) is a degenerative joint disease characterized by progressive loss of articular cartilage, subchondral bone sclerosis, osteophyte formation, and synovial inflammation, causing substantial physical disability, impaired quality of life, and significant health care utilization. Traditionally, non-steroidal anti-inflammatory drugs (NSAIDs), including selective cyclooxygenase (COX)-2 inhibitors, have been used to treat pain and inflammation in OA. Besides its anti-inflammatory properties, evidence is accumulating that celecoxib, one of the selective COX-2 inhibitors, has additional disease-modifying effects. Celecoxib was shown to affect all structures involved in OA pathogenesis: cartilage, bone, and synovium. As well as COX-2 inhibition, evidence indicates that celecoxib also modulates COX-2-independent signal transduction pathways. These findings raise the question of whether celecoxib, and potentially other coxibs, is more than just an anti-inflammatory and analgesic drug. Can celecoxib be considered a disease-modifying osteoarthritic drug? In this review, these direct effects of celecoxib on cartilage, bone, and synoviocytes in OA treatment are discussed.